De‐ubiquitinases on the move: an emerging field in plant biology. (30th April 2020) - Majumdar, P.; Nath, U.
Abstract: A balance between the synthesis and degradation of active proteins governs diverse cellular processes in plants, spanning from cell‐cycle progression and circadian rhythm to the outcome of several hormone signalling pathways. Ubiquitin‐mediated post‐translational modification determines the degradative fate of the target proteins, thereby altering the output of cellular processes. An equally important, and perhaps under‐appreciated, aspect of this pathway is the antagonistic process of de‐ubiquitination. De‐ubiquitinases (DUBs), a group of processing enzymes, play an important role in maintaining cellular ubiquitin homeostasis by hydrolyzing ubiquitin poly‐proteins and free poly‐ubiquitin chains into mono‐ubiquitin. Further, DUBs rescue the cellular proteins from 26S proteasome‐mediated degradation to their active form by cleaving the poly‐ubiquitin chain from the target protein. Any perturbation in DUB activity is likely to affect proteostasis and downstream cellular processes. This review illustrates recent findings on the biological significance and mechanisms of action of the DUBs in Arabidopsis thaliana, with an emphasis on ubiquitin‐specific proteases (UBPs), the largest family among the DUBs. We focus on the putative roles of various protein–protein interaction interfaces in DUBs and their generalized function in ubiquitin recycling, along with their pre‐eminent role in plant development. Abstract :